The Effect of the Use of PowerPoint Media on the Interest in Learning History of Class X Students of SMA Negeri 1 Bumiayu - Khaerunnisa, Febrianan; Sunarjan, YYFR; Atmaja, Hamdan Tri (Universitas Negeri Semarang, 2021)
This research aimed to find out the learning interest for the History Lessons of students in X class SMA Negeri 1 Bumiayu before and after using PowerPoint media and to find out the effect of PowerPoint media on learning interest in History lessons of Students at SMA Negeri 1 Bumiayu. This type of research was quantitative, using an experimental research method in the form of a pre-experimental design and a one-group pre-test post-test design. The research population was all students in X class SMA Negeri 1 Bumiayu selected using a random sampling technique. Data collection techniques included observation, questioning, documentation, and literature. The data analysis technique used descriptive and inferential analysis techniques. Based on the analysis results, the first test (pre-test) generated an average of 52%, and the second test (post-test) was 68%. Besides the average percentage interest score, the test - t also showed that the value of count -8.479, based on distribution table t, value table for df = 35 was 2.042, and significant values were 0.000 < 0.05. With the value of count < table, it can be concluded that Ha is accepted and Ho is rejected, which means using PowerPoint media affects students' learning interests at SMA Negeri 1 Bumiayu.